Wild Coffea Species: A Modern Genomic Approach to Unravel Variations for Future Cultivated Coffee Improvement - Romain Guyot; Laura Gonzalez; Rickarlos Bezandry (Proceedings)
The genetic diversity of wild Coffea species holds immense potential for the enhancement of cultivated coffee trees, offering solutions to challenges such as disease resistance, climate adaptability, and yield improvement. This study leverages modern genomic approaches to investigate evolution and variations among wild Coffea species. By employing advanced sequencing technologies and comparative analysis, the aim was to understand the molecular evolution of these wild species, identifying key genes and genetic markers which contribute to desirable traits. This research integrates comprehensive genomic data analysis with field studies to provide an understanding of the genetic diversity within wild Coffea populations. The aim of this research is to target significant genetic variations that can be harnessed to develop superior coffee cultivars, ensuring sustainability and resilience in the face of changing environmental conditions. This study not only highlights the importance of preserving wild Coffea species but also underscores the role of genomic research in unlocking their potential for coffee breeding programs. By bridging the gap between conservation and cultivation, this work paves the way for future innovations in coffee agriculture.